Aggregation modes of anionic oxacarbocyanines with polycations in solution and in ESAMs - Andrea Lodi; Glauco Ponterini (International Journal of Photoenergy)
Interaction of oxacarbocyanines D-G with three polycations in aqueous solutions results in the formation of two types of likely small, distorted aggregates rather than the classical J aggregates. On the contrary, the latter are extensively and almost exclusively obtained in electrostatically self-assembled multilayers (ESAMs) prepared by alternate polycation/dye adsorption on quartz substrates. The J-aggregate growth on supported polycations is qualitatively shared by the four cyanines, a fact that reveals the crucial role of the double anionic substitutions on the dyes. On the other hand, films with D and E, which are known to have a stronger tendency to give dimers in water, exhibit higher J-band intensities and stability upon drying relative to those with F and G. Based on these observations, we suggest that energetic factors associated with cofacial dye/dye van der Waals interactions, ultimately related with the degree of planarity of the conjugated chromophores, may still play a major role in controlling aggregation equilibria in these complex systems.